Modification of CaO from Scallops (Amusium Pleuronectes) with Fe3O4 and SiO2 for Adsorption of Congo Red and Methylene Blue Dye - Fera Rahma Sari; Widia Purwaningrum; Addy Rachmat (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Congo Red and Methylene Blue dye waste from the textile industry needs to be treated before being discharged into water bodies. Adsorption is widely recognized as an effective method of contaminant removal. The use of CaO as an adsorbent has the advantages of high kinetic speed, efficient, low cost, easily accessible, and abundant. To improve the performance of CaO, it is done by compositing CaO with Fe3O4 and SiO2. This study aims to synthesize a CaO/Fe3O4/SiO2 and apply it for the adsorption of Congo red and Methylene blue dyes. The synthesis of CaO/Fe3O4 uses the coprecipitation method and CaO/Fe3O4/SiO2 is synthesized using the Stober method by adding TEOS to CaO/Fe3O4. The results of XRD characterization show that the synthesized CaO, CaO/Fe3O4, and CaO/Fe3O4/SiO2 have the same 2θ angle as the reference diffractogram data. The addition of SiO2 was shown to prevent agglomeration, which was indicated by a decrease in the particle size of CaO/Fe3O4 from 70.07 to 52.42 nm in CaO/Fe3O4/SiO2. % Adsorption efficiency for Congo Red was 86.49% Methylene Blue was 99.12%. The adsorption process of both dyes was spontaneous, following a pseudo-second-order kinetic model. Congo Red adsorption followed the Freundlich isotherm model, while Methylene Blue followed the Langmuir isotherm model.Keywords: CaO/Fe3O4/SiO2, adsorption, Congo red, Methylene blue